(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to examine the effectiveness of using Virtual Reality (VR) in teaching speaking and grammar to students in the context of English as a Foreign Language (EFL). The study uses a quasi-experimental design involving an experimental group and a control group. The experimental group received VR-based learning, while the control group was taught using conventional learning methods. The research subjects were students who took English courses. Data were collected through speaking and grammar tests administered in the form of pre-tests and post-tests. The data obtained were analyzed using descriptive statistics to see the trend of improvement in ability, as well as inferential statistical tests in the form of paired sample t-tests and independent sample t-tests to determine the difference in learning outcome improvement between the two groups. The results showed that students in the experimental group experienced a more significant improvement in speaking and grammar proficiency compared to the control group. These findings indicate that Virtual Reality is capable of creating an immersive and contextual learning experience that supports the development of fluency and grammatical accuracy. This study concludes that Virtual Reality can be effectively integrated into English language learning in higher education to improve students’ communicative competence.